Effective Design of Educational Virtual Reality Applications for Medicine using Knowledge-Engineering Techniques. Issue 2 (2017) - Górski, Filip; Buń, Paweł; Wichniarek, Radosław; Zawadzki, Przemysław; Hamrol, Adam
No abstract available